Effects of the murine skull in optoacoustic brain microscopy. Issue 1 (27th April 2015) - Kneipp, Moritz; Turner, Jake; Estrada, Héctor; Rebling, Johannes; Shoham, Shy; Razansky, Daniel
Abstract : Despite the great promise behind the recent introduction of optoacoustic technology into the arsenal of small‐animal neuroimaging methods, a variety of acoustic and light‐related effects introduced by adult murine skull severely compromise the performance of optoacoustics in transcranial imaging. As a result, high‐resolution noninvasive optoacoustic microscopy studies are still limited to a thin layer of pial microvasculature, which can be effectively resolved by tight focusing of the excitation light. We examined a range of distortions introduced by an adult murine skull in transcranial optoacoustic imaging under both acoustically‐ and optically‐determined resolution scenarios. It is shown that strong low‐pass filtering characteristics of the skull may significantly deteriorate the achievable spatial resolution in deep brain imaging where no light focusing is possible. While only brain vasculature with a diameter larger than 60 µm was effectively resolved via transcranial measurements with acoustic resolution, significant improvements are seen through cranial windows and thinned skull experiments.(a) Experimental setup for hybrid acoustic and optical resolution optoacoustic microscopy. (b) Transcranial scan of an adult mouse brain using the optical resolution mode. Scale bar is 375 µm. Abstract : A range of distortions introduced by an adult murine skull in transcranial optoacoustic microscopy studies under both acoustically‐ and optically‐determined resolution scenarios is examined. It is shown that strong low‐pass filtering characteristics of the skull may significantly deteriorate the achievable spatial resolution in deep brain imaging where no light focusing is possible.